An unusual reduction in the mesospheric semi-diurnal tidal amplitude over Tirunelveli (8.7°N, 77.8°E) prior to the 2011 minor warming and its relationship with stratospheric ozone - Sridharan, S.; Sathishkumar, S.; Gurubaran, S. (My University, 2012)
There is an unusual decrease of semi-diurnal tidal amplitude in zonal wind at 88 km over Tirunelveli (8.7°N, 77.8°E) prior to the onset of a minor warming event of 2011. During that time, there is a sudden decrease of TIMED-SABER observed ozone volume mixing ratio (VMR) at equator and 60°N. It is suggested that the enhanced planetary wave activity prior to the occurrence of SSW increases the strength of the Brewer–Dobson circulation, which transports stratospheric ozone, the solar insolation absorption of which mainly generates semi-diurnal tide, to high-latitude lower stratosphere and as expected, ozone VMR at 70°N increases in the lower stratosphere.
Keywords: Stratospheric sudden warming; Ozone; Mesospheric tides; Brewer-Dobson circulation; Tirunelveli